Ubiquitous Language Learning for Global Communities: Mobile Learning as a Tool for Cross Cultural Communication and Language Proficiency - Maya Nguema; Koffi Makaya; Wawan Hendrawan (International Journal of Language and Ubiquitous Learning, 2026)
Background. In a globalized world, language learning extends beyond traditional classrooms, requiring more flexible, accessible, and culturally inclusive methods. Mobile learning (m-learning) has emerged as a powerful tool for language acquisition, offering learners the ability to engage with content anytime and anywhere. Additionally, it facilitates cross-cultural communication by providing diverse cultural contexts, helping learners understand not only the language but also the social and cultural nuances that shape its use. Purpose. This study aims to explore the role of mobile learning as a tool for enhancing cross-cultural communication and language proficiency. The research seeks to evaluate how mobile applications, through interactive and context-based learning, promote language skills and cultural understanding, preparing learners for effective communication in global communities. Method. A mixed-methods approach was employed, combining quantitative analysis of language proficiency improvement through mobile learning apps and qualitative data from surveys and interviews to assess cultural engagement. The study involved 120 participants who used a mobile language learning app for 8 weeks. Results. The findings reveal that mobile learning significantly improved learners' language proficiency, particularly in vocabulary, speaking, and listening. Additionally, participants reported increased cultural awareness and confidence in cross-cultural interactions, highlighting the effectiveness of mobile learning in bridging cultural gaps. Conclusion. Mobile learning serves as an effective tool for language proficiency and cross-cultural communication, providing accessible, immersive, and contextually rich learning experiences for global communities.